Metaphors Instrumental in Achieving the Pragmatic Effect in Animal Rights Advertisements - Oļehnoviča, Ilze; Tretjakova, Jeļena; Liepa, Solveiga (Research in Language, 2020)
Metaphor can manifest itself in a variety of form including the visual one, which can be an extremely expressive means of communication. That is why visual metaphors are widely used by marketers and advertisers thus becoming a topical object of linguistic research programmes. The study of visual metaphor is tightly related to the study of conceptual metaphor as the target message delivered by a picture is derived from a certain source field that is employed for metaphorical representation. Another type of metaphor commonly used in visual representation is a multimodal metaphor. The present research dwells upon the study of metaphor use in animal rights protection advertisements. The hypothesis of the study is that visual metaphors present strong content that can activate emotions and contribute to the marketers’ desire to influence the audience.